Auroramycin: A Potent Antibiotic from Streptomyces roseosporus by CRISPR‐Cas9 Activation. (27th June 2018) - Lim, Yee Hwee; Wong, Fong Tian; Yeo, Wan Lin; Ching, Kuan Chieh; Lim, Yi Wee; Heng, Elena; Chen, Shuwen; Tsai, De‐Juin; Lauderdale, Tsai‐Ling; Shia, Kak‐Shan; Ho, Ying Swan; Hoon, Shawn; et al.
Abstract: Silent biosynthetic gene clusters represent a potentially rich source of new bioactive compounds. We report the discovery, characterization, and biosynthesis of a novel doubly glycosylated 24‐membered polyene macrolactam from a silent biosynthetic gene cluster in Streptomyces roseosporus by using the CRISPR‐Cas9 gene cluster activation strategy. Structural characterization of this polyketide, named auroramycin, revealed a rare isobutyrylmalonyl extender unit and a unique pair of amino sugars. Relative and absolute stereochemistry were determined by using a combination of spectroscopic analyses, chemical derivatization, and computational analysis. The activated gene cluster for auroramycin production was also verified by transcriptional analyses and gene deletions. Finally, auroramycin exhibited potent anti‐methicillin‐resistant Staphylococcus aureus (anti‐MRSA) activity towards clinical drug‐resistant isolates. Abstract : Turn up the noise ! Silent biosynthetic gene clusters represent a potentially rich source of new bioactive compounds. A potent anti‐methicillin‐resistant Staphylococcus aureus (anti‐MRSA) doubly glycosylated 24‐membered polyene macrolactam, named auroramycin, is obtained from Streptomyces roseosporus by using a CRISPR‐Cas9 gene cluster activation strategy.